CBE670: Food Science and Technology / College of Engineering - UiTM, College of Engineering (2021)
This is an introductory course in food science and technology. It covers an introduction to the food processing industry, food constituents, composition and processing of different food commodities, sensory and nutritional aspects, food safety and legislation, packaging of food product and product development in food industries.